Moderate and heavy alcohol consumption among Turks: long-term impact on mortality and cardiometabolic risk - Onat, Altan; Hergenc, Gulay; Kucukdurmaz, Zekeriya; Ugur, Murat; Kaya, Zekeriya; Can, Gunay; Yuksel, Husniye (KARE PUBL, 2009)
Objectives: The impact of alcohol consumption on various outcomes was prospectively evaluated in the participants of the Turkish Adult Risk Factor Study. Study design: A total of 3,443 men and women (mean age 47.6 +/- 12 years) were included at baseline and followed-up for a mean of 7.4 years (range 5 to 9 years). Alcohol drinking status was assessed as abstention and brackets of moderate and heavy intake. Only 19.5% of adults (35% of men and 4.2% of women) reported consumption of alcohol. In each multivariate analysis, individuals with the examined endpoint at baseline were excluded, and alcohol drinking status was adjusted for age, sex, smoking status, and physical activity. Results: Alcohol intake increased overall mortality (by 2-fold) in men drinking heavily, but not in men drinking moderately, nor in women. Heavy drinking in combined sexes predicted the risk for incident coronary heart disease (CHD) (RR 2.3; 95% CI 1.30; 4.05), while moderate drinking tended to be protective (RR 0.72; 95% CI 0.50; 1.035). Heavy intake predicted incident diabetes risk (RR 2.13) and tended to be so for new metabolic syndrome (MetS) in men (RR 1.71), whereas moderate alcohol intake was not significantly associated with subsequent development of diabetes or MetS and the risk for MetS was reduced in women (p=0.10). Conclusion: Risk of alcohol intake depends on the amount used: heavy intake raising the risk for diabetes and CHD in combined sexes, and overall mortality in men, contrasted to moderate intake reducing (borderline) the CHD risk and marginally reducing all-cause mortality. Risk for MetS tends to be reduced in women alone.
Keywords: Alcohol drinking; cholesterol; HDL; coronary disease; diabetes mellitus; type 2; metabolic syndrome X; mortality; risk factors; Turkey/epidemiology; HIGH-DENSITY-LIPOPROTEIN; METABOLIC SYNDROME; CARDIOVASCULAR-DISEASE; NATIONAL-HEALTH; BLOOD-PRESSURE; METAANALYSIS; MEN; DRINKING; US; Cardiovascular System & Cardiology